Penta Helix Collaboration in Coastal Waste Management for Sustainable Empowerment of Traditional Fishing Families - Dara Aisyah; Elisa Julianti; Februati Trimurni; Muhammad Sontang Sihotang; M Deny Effendy Tambusay (Universitas Teuku Umar, 2026)
This study implements the Penta-Helix collaborative model in an empowerment program for traditional fishing households in Medang Deras Subdistrict, Batubara Regency, North Sumatra Province, through innovative interventions in coastal waste management, transforming waste into calcium-based products. The study aims to address suboptimal coastal waste management and the economic marginalization of fishing communities. The model engages five key actors: the Batubara Regency Government, academics from the University of Sumatera Utara, the private sector represented by PT Indonesia Asahan Aluminium, traditional fishing communities, and media personnel affiliated with the Indonesian Journalists Association. Employing an action research methodology, the study began with surveys, observations, interviews, and focus group discussions with the Penta-Helix actors, followed by empowerment interventions through structured training in coastal waste management. The intervention was implemented via knowledge transfer and training across four stages: (1) collection of coastal waste, (2) processing waste into calcium powder, (3) application of innovative products to meet household needs, and (4) continuous mentoring. The findings indicate that the innovation intervention significantly enhanced local knowledge and skills, increased environmental awareness, and fostered entrepreneurial capacities within traditional fishing households. Moreover, the Penta-Helix actor collaboration successfully established innovation-driven community groups acting as ambassadors to expand the program’s impact. The study recommends institutionalizing the Penta-Helix model within regional development strategies, complemented by fiscal incentives, to strengthen inclusive and sustainable coastal economies.